Karakter Siswa Ditinjau Dalam Toleransi Beragama Dan Multikulturalisme: (Penelitian Pada Siswa SMA Al Ashriyyah Nurul Iman Parung Kabupaten Bogor ) - Apudin, Apudin; Maksum, Ghufron (Al Ashriyyah, 2022)
This research aims to determine and test empirical data related to the relationship of religious tolerance and understanding of multiculturalism with the character of students separately or simultaneously. In this research, the authors used a quantitative method with a correlational approach in the form of cluster rondom sampling technique on quantitative data obtained from the object of research, namely students at SMA Al Ashriyyah Nurul Iman Parung Bogor regency. The sample of this research was 104 respondents from a total population of 140 students of SMA Al Ashriyyah Nurul Iman Parung Bogor Regency. Data collection was carried out using survey methods and questionnaires. The type of analysis used is correlational analysis and regression which are described descriptively. The results of this research First, there are positive and significant relationship between religious tolerance on student character. Second, there are positive and significant relationship between the understanding of multiculturalism on student characteristics. Third, there are positive and strong and significant relationship between religious tolerance (X1) and the understanding of multiculturalism (X2) together on student character (Y)